Interdisciplinary approach for complex esthetic periodontal or prosthodontic treatment: a case report - Alghamdi, Hamdan (International Journal Of Community Medicine And Public Health, 2022)
Patients with a complex periodontal/restorative esthetic condition can only be successfully treated with an interdisciplinary approach. This report presents case managed with varying levels of periodontal and prosthodontic coordination of care. A 48-year-old female patient with no medical conditions, presented chiefly to enhance her dental esthetics and eliminate the central diastema. There was also gingival asymmetry and altered passive eruption (APE). High frenal attachment was also noticed in relation the central diastema space. The depigmentation, gingivectomy, and gingivoplasy procedures were planned accordingly. After 3 months of periodontal healing, the patient returned for the final porcelain veneer restorations limiting to the upper anterior incisors. The treatment of the complex periodontal/prosthetic esthetic patient can be achieved with an interdisciplinary approach. Such a dental rehabilitation should be beginning by a comprehensive esthetic examination. Then an accurate diagnosis, prognosis evaluation, and treatment planning have to be identified. In addition, the utilization of an advanced surgical and restorative biomaterials will ensure the best result with patient satisfaction.